2021
DOI: 10.1007/s11240-021-02159-3
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid induces somatic embryogenesis and enables the capture of high-value genotypes in Douglas fir (Pseudotsuga menziesii [MIRB.] Franco)

Abstract: Douglas fir (Pseudotsuga menziesii) is one of Europe’s most important non-native tree species due to its drought tolerance as well as timber quality and yield. To obtain superior seed from selected parental trees, breeding programs had been established in seed orchards. Douglas fir seed is used as source material for somatic embryogenesis with the aim to select elite genotypes invaluable for clonal mass propagation. To improve given protocols for somatic embryo initiation, we used immature Douglas fir zygotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Studies have shown that it is associated with embryo development and maturation [71]. We also observed an increase in relative ABA levels from y to f stages of both genotypes (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown that it is associated with embryo development and maturation [71]. We also observed an increase in relative ABA levels from y to f stages of both genotypes (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…However, as in most conifer species (see Bonga et al, 2010 ), initiation of somatic embryogenesis in P. pinaster materials older than immature zygotic embryos ( Trontin et al, 2016c ) or cotyledonary or young germinating SEs ( Klimaszewska et al, 2009 ) is still difficult to achieve and may require the additional use of PGRs such as auxin and/or cytokinins. Recently, it was shown that abscisic acid (ABA) supplementation can also lead to initiation of somatic embryogenesis in the Douglas fir ( Pseudotsuga menziesii ) ( Walther et al, 2021 ) and has to be taken into consideration as a signal for SE activation. Induction of secondary somatic embryogenesis from germinated SEs could be obtained but at low rate with a combination of 2,4-D (9.5 μM) and BA (4.5 μM) in P. pinaster ( Klimaszewska et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each sample was sectioned serially at 8 µm on a microtome (Leica RM2016, Tokyo, Japan). Subsequently, sections were stained with Ehrlich hematoxylin using the method described in a previous report [22]. The prepared slides were observed and photographed using a light microscope (NI/E, Nikon, Tokyo, Japan).…”
Section: Histology Of Amo1-proliferated Callusmentioning
confidence: 99%